Thiazide Diuretics and the Incidence of Osteoporotic Fracture: A Systematic Review and Meta-Analysis of Cohort Studies - Wang, Jun; Su, Ke; Sang, Weihua; Li, Longjie; Ma, Shiyun (Frontiers in Pharmacology, 2019)
Background: Thiazide diuretics may improve bone mineral density. However, results are inconsistent for studies evaluating the association between thiazides and risk of osteoporotic fracture. We performed an updated meta-analysis of cohort studies to determine the association between thiazides use and fracture risk. Methods: Relevant studies were identified via systematic search of PubMed and Embase. A random-effect model was used for meta-analysis. Subgroup analyses were performed to explore the potential influences of study characteristics on the outcome. Results: Seventeen cohort studies with 3,537,504 participants were included. The pooled results showed that use of thiazide diuretics at baseline did not significantly affect the risk of overall osteoporotic fracture incidence as compared with controls (risk ratio [RR]: 0.96, 95% confidence interval [CI]: 0.83 to 1.09, p = 0.51) with significant heterogeneity (p for Cochrane’s Q test < 0.001, I2 = 90%). Results of subgroup analyses indicated that general status of the participants may be an important determinant for the association between thiazide diuretics and subsequent risk of osteoporotic fracture. Use of thiazide diuretics was associated with significantly reduced risk of fracture in patients with acute status including new-onset stroke or spinal cord injury (RR: 0.70, 95% CI: 0.57 to 0.86, p < 0.001), but not in those with good conditions such as community-dwelling population or hypertensive patients (p for subgroup difference = 0.02). Conclusions: Use of thiazide diuretics are not associated with significantly affected risk of overall osteoporotic fracture. However, the association may be different according to the general status of the participants.